Distinct metabolic profiles of circulating plasmacytoid dendritic cells in systemic sclerosis patients stratified by clinical phenotypes - Ferreira, Beatriz H. (2025)
Funding Information: This work was supported by the World Scleroderma Foundation and Edith Busch Stiftung (the EBF and WSF Research Grant Programme 2022\u20132023). Work developed within the scope of iBiMED \u2013 Institute of Biomedicine (references UIDB/04501/2020, DOI https://doi.org/10.54499/UIDB/04501/2020 , UIDP/04501/2020, DOI https://doi.org/10.54499/UIDP/04501/2020 ), CICECO \u2013 Aveiro Institute of Materials (UIDB/50011/2020, DOI https://doi.org/10.54499/UIDB/50011/2020 ; UIDP/50011/2020, DOI https://doi.org/10.54499/UIDP/50011/2020 & LA/P/0006/2020, DOI https://doi.org/10.54499/LA/P/0006/2020 ), and LAQV-REQUIMTE (LA/P/0008/202, DOI https://doi.org/10.54499/LA/P/0008/2020 ; UIDP/50006/2020, DOI https://doi.org/10.54499/UIDP/50006/2020 ; UIDB/50006/2020, DOI10.54499/UIDB/50006/2020) and the project with the reference 2022.03217.PTDC (DOI https://doi.org/10.54499/2022.03217.PTDC ), financially supported by national funds (OE), through Funda\u00E7\u00E3o para a Ci\u00EAncia e a Tecnologia (FCT)/MCTES. FCT is also acknowledged for the individual grant to B.H.F. (SFRH/BD/144706/2019; DOI https://doi.org/10.54499/SFRH/BD/144706/2019 ) and the research contract under the Scientific Employment Stimulus to I.F.D. (CEECIND/02387/2018). Publisher Copyright: © The Author(s) 2025.